125k views
12 votes
6 =2 (y + 2) Solve Y

User LiveSource
by
5.0k points

2 Answers

9 votes

Answer:

y = 1

Explanation:

6 =2 (y + 2)

Distributive property ( multiply whatever is in the parenthesis, by the number outside of it, which in this case, will be 2)

6 = 2 * y + 2 * 2

6 = 2y + 4

Subtract 4 on both sides

6 - 4 = 2y + 4 - 4

2 = 2y

Divide by 2 on both sides to isolate the variable (y)

2/2 = 2y/2

1 = y

Check:

Substitute what you got for y into the equation

6 = 2 ( 1 + 2 )

6 = 2 * 3

6 = 6 CORRECT

Hope this helped!

Have a supercalifragilisticexpialidociuos day!

User Jonathan Graehl
by
5.5k points
5 votes

Answer:

y = 1

Explanation:

6 = 2y + 4

6 - 4 = 2y

2 = 2y

y = 2/2

y = 1

User Goclem
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.